2010
DOI: 10.1590/s0100-29452010005000078
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de genótipos de bananeira à Colletotrichum musae em pós-colheita

Abstract: , VICTOR MARTINS MAIA 9 RESUMO -Alguns hibridos tetraploides apresentam resistência à antracnose, porém são reduzidas as informações sobre os níveis de resistência desses genótipos e o comportamento dos mesmos no Brasil. O objetivo do presente trabalho foi avaliar a incidência e a severidade de antracnose sobre o comportamento de diferentes genótipos de bananeiras resistentes a Sigatoka-Negra em função de diferentes concentrações de conídios de Colletotrichum musae em diferentes épocas de avaliação. Os frutos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…On the other hand, the genotypes Caipira, Thap maeo and Fhia 18 presented greater resistance to the fungus, and consequently, a superior shelf life. Studies performed by Pinho et al (2010) demonstrated that the genotype Thap Maeo showed less severity (27.5%) to anthracnose, while the genotypes Fhia 18 was the most susceptible, with 61.33% severity levels. Studies by several authors have shown the importance of the exploitation of these genotypes mainly because they are resistant to Mycosphaerella fijiensis (PINHO et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the genotypes Caipira, Thap maeo and Fhia 18 presented greater resistance to the fungus, and consequently, a superior shelf life. Studies performed by Pinho et al (2010) demonstrated that the genotype Thap Maeo showed less severity (27.5%) to anthracnose, while the genotypes Fhia 18 was the most susceptible, with 61.33% severity levels. Studies by several authors have shown the importance of the exploitation of these genotypes mainly because they are resistant to Mycosphaerella fijiensis (PINHO et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The authors reported only the incidence on day seven, without comparing orchards, harvests or consider a possible tree effect. Similarly, Pinho et al (2010) evaluated the incidence of Colletotrichum musae in nine banana genotypes inoculated with six inoculum concentrations in two evaluation dates, in a factorial design allowed by variance.…”
Section: Days Aftermentioning
confidence: 99%